Multifaceted effects of chronic radiation exposure in Japanese red pines from Fukushima prefecture - Geras'kin, Stanislav; Yoschenko, Vasyl; Bitarishvili, Sofia; Makarenko, Ekaterina; Vasiliev, Denis; Prazyan, Alexandr; Lychenkova, Maria; Nanba, Kenji (The Science of the total environment, 2021)
Despite many studies carried out to date, the long-term effects of chronic exposure on plants and animals inhabiting the territories affected by the Fukushima Dai-Ichi NPP accident remain the subject of scientific discussions. Our investigations were performed on Japanese red pine, the native tree species that is widely spread in the radioactive contaminated areas. Earlier observations revealed the radiation-induced cancellation of the apical dominance in young trees of this species. To understand the mechanism of such transformation, we evaluated the morphometric parameters of needles, the frequency of cytogenetic abnormalities, and the concentrations of the major classes of phytohormones in several natural populations of young red pine trees growing under different exposure conditions in Fukushima prefecture. No significant relationships between the morphometric parameters of needles and dose rates at the experimental sites were revealed. The frequencies of aberrant cells in the needle's intercalary meristem and the frequencies of cancellation of the apical dominance in the young pine populations in the radioactive contaminated areas were significantly higher than in the reference population. However, only cytogenetic abnormalities increased with the dose rate. We have not found the relation between the frequency of cytogenetic abnormalities in needles and cancellation of the apical dominance in the individual trees. In this paper, for the first time, it is shown that chronic radiation exposure changes the concentration ratio of the major classes of phytohormones in the needles of Japanese red pine. Given the complete lack of information about the most important regulatory system of plants in chronically irradiated populations, this study fills a substantial gap in our knowledge. Finally, our findings indicated that the most probable causes of the cancellation of apical dominance observed in chronically exposed Japanese red pines are radiation damage to the apical meristems of the trees and changes in their phytohormonal balance. [Display omitted] •Effects of chronic exposure on Japanese red pine from Fukushima were investigated.•No relationship between morphometric parameters of needles and dose rate was found.•The aberrant cells frequencies in pine needles increase with the dose rate.•Chronic radiation exposure changes the ratio of major classes of phytohormones.•Morphological effects in pines occur due to cytogenetic and phytohormonal changes.